Single-case study: Effectiveness of multilayer model to improve vocabulary knowledge of deaf students - Yohanes Subasno; Imanuel Hitipeuw (Intelektual Pustaka Media Utama, 2023)
This study aims to determine the effectiveness of implementing a multilayer model in lesson plan (LP) to increase the vocabulary knowledge of deaf students. This study is single-subject research with an A-B-A design (baseline-intervention-maintenance). The intervention instrument used was a LP that consisted of four units, each containing four words taught using multilayers. The instrument was validated and scored 4.6 on a scale of 1-5. The subjects who participated in the study were two students with severe deafness. Two teachers and two observers were involved in this study. The data were analyzed by inspecting the graph, intracondition, and intercondition. The percentage of non-overlapping data (PND) from the inter-condition was used to indicate the effectiveness of the intervention. It was found that the mean value of PND B/A for all LP from subject-1 was 96.25%, and from subject-2 was 100%. Thus, the multilayer model is very effective in improving vocabulary knowledge. The mean of PND A/B was 93.75%, and subject-2 achieved 89.87%, which means that the subject's vocabulary knowledge is maintained even without intervention.